Natural convection in porous triangular enclosure with a centered conducting body - Varol, Yasin (My University, 2011)
Poroz üçgen kapalı bir ortamda akış ve ısı tranferi analizi nümerik olarak incelenmiştir. Üçgen kapalı ortamın merkezine cisim yerleştirilmiştir. Yerleştirilen cismin yükseklik ve en oranlarına göre akış ve ısı transferi değerleri hesaplanmıştır.

A numerical work was performed to examine the heat transfer and fluid flow due to natural convection in a porous triangular enclosure with a centered conducting body. The center of the body was located onto the gravity center of the right-angle triangular cavity. The Darcy law model was used to write the governing equations and they were solved using a finite difference method. Results are presented by streamlines, isotherms, mean and local Nusselt numbers for the different parameters such as the Rayleigh number, thermal conductivity ratio, and height and width of the body. It was observed that both height and width of the body and thermal conductivity ratio play an important role on heat and fluid flow inside the cavity.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Gözenekli Ortam; Üçgen Kapalı Ortam; Doğal Taşınım